2015
DOI: 10.1016/j.amjcard.2015.01.555
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Regional Distribution of Coronary Artery Calcium to Improve the Prediction of All-Cause Mortality

Abstract: Background: While the traditional Agatston coronary artery calcium (CAC) score is a powerful

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 22 publications
1
30
0
3
Order By: Relevance
“…This should include registry studies of clinical CAC scanning, as most clinical cardiac CT centers have routinely reported CAC on a per-vessel basis 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should include registry studies of clinical CAC scanning, as most clinical cardiac CT centers have routinely reported CAC on a per-vessel basis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The traditional Agatston CAC score has persisted for decades, but emerging evidence has suggested novel ways of improving the score 28 . An advantage of simple consideration of number of vessels with CAC is that it also easy to quantify on non-gated chest CTs ordered for non-cardiac indications, which is a rapidly expanding application of CAC scoring 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The simple CAC-DRS integration of severity and dispersion of CAC was proposed based on studies from the multi-Ethnic Study of Atherosclerosis (MESA), which showed that number of vessels with CAC have prognostic significance beyond absolute CAC score, particularly in the CAC range of 1-300. 12,13 For this study, the CAC-DRS categories were defined using A X /N Y scoring (using Agatston score data and number of vessels with CAC). Therefore, CAC-DRS scores ranged from A0 to A3/N4.…”
Section: Definition Of Cac-drs: Coronary Artery Calcium Data and Repomentioning
confidence: 99%
“…Further, a retrospective study of 23,057 patients found a significant relationship between the number of coronary arteries (right, left main, left anterior and left circumflex) with calcification in each patient and all‐cause mortality within 7 years of the initial measurement of calcium burden (Tota‐Maharaj et al . ). The compiled data from these studies suggest a strong link between cardiovascular calcification and morbidity/mortality that has challenged previously held notions that calcification stabilizes atherosclerotic plaques.…”
Section: Vascular Calcification Predicts Cardiovascular Morbidity Andmentioning
confidence: 97%